Telecommuting and labor performance on covid-19 framework - Chuco Aguilar, Victoria Judith (2021)
Telecommuting allows employees to do work from home. In a COVID-19 pandemic context, telecommuting has become the main working mode in organizations. This fact represents a challenge for maintaining employee productivity, due to labor pressures and market uncertainty. Two main factors emerge from this analysis: the organization´s capacity to establish adequate communication systems, and the ability of the employee to manage his or her emotions under uncertainty.